PEMANFAATAN REMOTE SOURCE SOLAR LIGHTING (RSSL) UNTUK PENGHEMATAN ENERGI DI GEDUNG KOMERSIAL - Busono, Suryo; Hilmawan, Edi (Jurnal Energi dan Lingkungan (Enerlink), 2015)
Remote Source Solar Lighting (RSSL) is an innovation in lighting technology in the building to transfernatural light into areas which are not covered by conventional natural lighting techniques. In this study,RSSL applications in an Office Building in the Puspiptek Area Tangsel has been examined.Measurement and simulation are used evaluate the effectiveness of the use of RSSL in illuminatingareas that do not have access to outside light. Advanced simulation was conducted to compare theuse of artificial light to produce the same illumination level. The measurement results show that theSolar Light Collector combined with Light Tube is able to transfer light from the outside into the roomwith a level of efficiency of 39.48%. Utilization of light focusing module can improve the efficiency oflight distribution with an efficiency of up to 56.1%.The simulation results show that RSSL with light tubediameter of 35 cm, capable of illuminating an area that does not have access to the outside withillumination level up to 219 Lux at the zenith ilumination of 89000 Lux. However, RSSL is no longereffective when the zenith illumination down to 26000 Lux. Comparison between CFL bulbs with RSSL,with the same lighting point, when the zenith illumination levelis average or higher, RSSL providelighting levels on par with CFL bulbs, but still lower than the LED lights. When the zenith illumination islow / minimal then 14 points RSSL only able to provide lighting equivalent to 8 points CFL.Key Words: Energy conservation in commercial building, smart building, natural lighting, RemoteSource Solar Lighting